Formulación de estrategias para el mejoramiento de la calidad en el ciclo del medicamento en Instituciones Prestadoras de Servicios de Salud (2009)
Medication errors increase the morbidility and mortality problems associated costs for the hospitals. The objective of this study is to establish its frequency and impact on the patients and to seek strategies to decrease its incidence. Three methods were used: direct observation, interviews to healthcare providers and incident reports in the use of medication by the hospital staff in pediatric pharmacy services in two hospitals from Bogotá D.C. The main errors identified during the medicines cycle were: in the prescribing process, wrong filling of the prescription related to the person who is prescribing, patient and medicine; at the supply stage, not checking the amount of medicine given by the pharmacy to the nurses; and in the medicines administration process, wrong schedules for medicine administration. The first step in order to decrease medication errors is to treat the problem in different interdisciplinary levels inside the hospitals, in order to implement effective programs to detect, evaluate and prevent medication errors.